Frontier follies adventures in marriage & motherhood in the middle of nowhere - Drummond, Ree (New York, NY : William Morrow, an Imprint of HarperCollinsPublishers, 2020)
"In this relatable, charming book, Ree unveils real goings-on in the Drummond house and around the ranch. In stories brimming with the lively wit and humor found in her cookbooks and her bestselling love story, The Pioneer Woman: Black Heels to Tractor Wheels, Ree pulls back the curtain and shares her experiences with childbirth, wildlife, isolation, teenagers, in-laws, and a twenty-five-year marriage to a cowboy/rancher." -- Amazon.com.
The Food Network star shares heartwarming stories and reflections about her life in the country with her four children and rancher husband.
Marriage -- Motherhood -- The whole fam damily -- Country life -- New territory.
108493
Keywords: Drummond, Ree; Ranch life -- Oklahoma -- Biography; Marriage; Motherhood; Families; Personal Memoirs; Women; Autobiographies; Anecdotes